Creativity of Physical Education Teachers in Elementary School Learning in Kaliwungu District - Nanik Iryanti; Tandiyo Rahayu; Donny Wira Yudha Kusuma (Journal of Physical Education and Sports, 2022)
Qualified educators are needed to develop educational progress. The purpose of this research is to analyze the ability factors of PE teachers in elementary school learning, to analyze the driving factors of the PE teacher's school environment in elementary learning, to analyze the open attitude of accepting new things for PE teachers. Quantitative descriptive research method. Analysis of qualitative data and numerical data using quantitative analysis. Data sources in this study were school principals, PE teachers, and elementary school students in Kaliwungu District. Qualitative data collection techniques are observation, interviews, and documentation. The results of the PE teacher's ability factor research obtained a reliability value of 0.88, so the PE teacher's ability factor was classified as good. Of the 23 PE teachers, 5 teachers have very high teaching abilities, 12 teachers were classified as high, and 6 teachers as moderate. The school environment push factor has a reliability value of 0.912, so the school environment push factor is classified as good. 7 PE teachers use the school environment very highly, 9 teachers were classified as high, and 7 PE teachers were classified as moderate. The attitude factor for accepting new things has a reliability value of 0.95, so the attitude factor for accepting new things is special. 5 PE teachers accepted new things highly, 15 PE teachers were classified as high, and 3 PE teachers as moderate. Conclude that of the three PE teacher creativity factors, there are no teachers who are classified as low or very low.